Teacher Technology and Communication Utilisation: A Review of Teacher Implementation In 21st Century Elementary Schools - Adrian, Elfira Rosa; Sain, Zohaib Hassan (Nur Science Institute, 2024)
Background:This study aims to describe studies related to how ICT is utilized and the obstacles to the utilization of ICT in 21st century learning in elementary schools. Method:This study uses a qualitative descriptive approach and a type of library research or (literature review). The data analysis technique used is content analysis. The validity of the data used is the persistence of observation and triangulation of sources. Result:The results of the study showed that some teachers have used learning media, both ICT and NON-ICT, to support learning, some class teachers do not use learning media for reasons of limited costs and inefficiency in making media, as well as inadequate ICT skills of teachers, hindering communication between teachers and students or even between students, the possibility of misuse of the use of ICT media in the field of education. In the use of computer media, there are obstacles and constraints such as application errors when used, and technical symptoms of electricity such as power outages. Communication that occurs in learning is still less effective, because in some classes there are still students who are embarrassed to ask, or no one asks questions, so the teacher assumes that students already understand the material that has been delivered. Implication:This study is the importance of improving teacher competence in utilizing ICT optimally to support 21st century learning in elementary schools. The results of this study indicate that although the use of ICT can improve the quality of learning, there are various obstacles, such as limited facilities and lack of teacher ability to integrate technology effectively. Novelty:This research is based on an in-depth understanding of the challenges faced in implementing ICT in primary schools, especially in rural areas, which provides new insights for the development of more targeted policies and training.